Evaluation of arazá (Eugenia stipitata Mc Vaugh) fruit behaviour after wet postharvest conditioning operations - Peña, Adriana Carolina; González, María Lucía; Hernández, María Soledad; Novoa, Carlos; Quicazán, Marta C.; Fernández-Trujillo, Juan Pablo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2011)
Arazá fruits are coming from the departments of Caquetá and Putumayo in Colombia. They were selected and classified according to maturity index. Then, half of them were conditioned, and washed by immersion with tap water for 5 min, right after, they were sanitized with 100 ppm of sodium hypochlorite, and rinsed later to remove any residuals. Finally, residual humidity was removed by natural convection at room temperature. Fruits were stored for seven days at 13±1ºC and 95% HR±1. The conditioned fruits presented less decay than the controlled ones.